CRISPR-Cas9 gene editing strengthens cuproptosis/chemodynamic/ferroptosis synergistic cancer therapy - Xiaoyu Wu; Zijun Bai; Hui Wang; Hanqing Wang; Dahai Hou; Yunzhu Xu; Guanqun Wo; Haibo Cheng; Dongdong Sun; Weiwei Tao (Elsevier, 2024)
Copper-based nanomaterials demonstrate promising potential in cancer therapy. Cu+ efficiently triggers a Fenton-like reaction and further consumes the high level of glutathione, initiating chemical dynamic therapy (CDT) and ferroptosis. Cuproptosis, a newly identified cell death modality that represents a great prospect in cancer therapy, is activated. However, active homeostatic systems rigorously keep copper levels within cells exceptionally low, which hinders the application of cooper nanomaterials-based therapy. Herein, a novel strategy of CRISPR-Cas9 RNP nanocarrier to deliver cuprous ions and suppress the expression of copper transporter protein ATP7A for maintaining a high level of copper in cytoplasmic fluid is developed. The Cu2O and organosilica shell would degrade under the high level of glutathione and weak acidic environment, further releasing RNP and Cu+. The liberated Cu+ triggered a Fenton-like reaction for CDT and partially transformed to Cu2+, consuming intracellular GSH and initiating cuproptosis and ferroptosis efficiently. Meanwhile, the release of RNP effectively reduced the expression of copper transporter ATP7A, subsequently increasing the accumulation of cooper and enhancing the efficacy of CDT, cuproptosis, and ferroptosis. Such tumor microenvironment responsive multimodal nanoplatform opens an ingenious avenue for colorectal cancer therapy based on gene editing enhanced synergistic cuproptosis/CDT/ferroptosis.